Temperature‐Mediated Dynamic Lithium Loss and its Implications for High‐Efficiency Lithium Metal Anodes - Zhang, Shuo; Ding, Jun‐Fan; Xu, Rui; Xiao, Ye; Yan, Chong; Huang, Jia‐Qi (Advanced energy materials, 2024)
Lithium (Li) metal has been strongly regarded as the ultimate anode option for next‐generation high‐energy‐density batteries. Nevertheless, the insufficient Coulombic efficiency induced by the extensive active Li loss largely hinders the practical operation of Li metal batteries under wide temperature range. Herein, the temperature‐mediated dynamic growth of inactive Li from −20 to 60°C via titration gas chromatograph measurements is quantitatively decoupled. Combined X‐ray photoelectronic spectroscopy, cryo‐transmission electronic microscopy, and scanning electronic microscopy methods depicted that both solid electrolyte interphase (SEI) characteristics and Li deposition compactness can be profoundly manipulated by working temperature. The elevation of temperature is found to fundamentally aggravate the parasitic reactions and deteriorate the spatial uniformity of SEI, yet promote the lateral growth of Li by kinetic reason. The opposite effects of temperature on SEI properties and Li deposition compactness can properly explain the intricate temperature‐dependent growth rates of SEI‐Li+ and dead Li0 capacity loss observed under titration gas chromatograph measurements. Design implications towards more stable Li metal anodes with higher reversibility can thus be yielded. This work quantitatively decouples the dynamic evolution of Li loss at different temperatures by titration gas chromatograph. The opposite effects of temperature on SEI properties and Li deposition behavior determined intricate temperature‐dependent growth modes of SEI‐Li+ and dead Li0 capacity loss. The cognition provides guidance towards high‐efficiency Li metal anode under practical condition.